Regeneration Potential of the North Selangor Peat Swamp Forest (NSPSF) - Dahalan, Muhd. Puat (2001)
Peat Swamp Forest is known for its unique ecosystem and having a high proportion of endemic species. The logging activities in peat swamp forests has significant impacts on residual trees. A study was undertaken to determine the status of regeneration of logged-over forest of a peat swamp forest in Selangor. The study was conducted in the North Selangor Peat Swamp Forest (NSPSF), covering an area of approximately 72,816 hectares. The NSPSF was classified by the Forest Department to 7 categories of Forest Classes based on crown coverage. Based on this forest classification, a forest management inventory was carried out using cluster sampling technique. A total of 550 plots arranged in 110 clusters were randomly located within the seven forest classes. Data on tree species, diameter at breast height, height, quality of poles, etc. were collated. Results show that the number of stems per hectare (sph) for size class 5.0 em diameter at breast height (dbh) and above and size class 5.0-10.0 em dbh are in Forest Class 5. Wlereas for size class 10. 1-14.9 em dbh the highest number of sph is in Forest Class 4. The lowest number of sph for all size classes are in Forest Class 7. It is also found that more than 80% of the inventoried poles in all the Forest Classes are of Quality 1 and 2. As for poles of Quality 3 and 4, the highest percentage is in Forest Class 5 and the lowest in Forest Class 4. The number of seedlings per hectare are generally high with Forest Class 5 recording the highest at 19,621 and the lowest in Forest Class 7 at 7,133. The stocking of dipterocarp seedlings is very small with respect to all Forest Classes i.e. between o per cent in Forest Class 7 to 2.81 per cent in Forest Class 6. The nondipterocarp seedlings seem to dominate all Forest Classes in the NSPSF with an overall percentage of more than 97.0 per cent. The NSPSF suprisingly possess high q-value, calculated at an average of 1.73. The highest being recorded for Forest Class 4 at 1.93 and the lowest for Forest Class 7 at 1.65. The results of this study show that the NSPSF appears to have most of the elements of a forest undergoing regeneration process. Based on the q-value findings, the NSPSF has a good representation of smaller diameter size trees for all Forest Classes, thus further supporting the fact that the NSPSF is in a dynamic stage of recovering from the effect of forest disturbance. The only element which is absent as compared to a natural successional Peat Swamp Forest, is the lacking of sufficient number of high value commercial species for all size classes, which in this case refers to Shorea uliginosa, Gonystylus bancanus, Kompassia malaccensis and Shorea platycalpa. Some suggestions for future management of this type of forest are also highlighted.